The vertical run-off of rainfall through dolines - Kogovšek, Janja (Acta carsologica, 1996)
It was presumed that the abundant trickles are fed from the areas covered by dolines. Later was confirmed this by water tracing tests above Planinska Jama and Pivka Jama. The dolines above Planinska Jama, separated from the cave by a 100 m thick layer of limestones, drain the rainfall water fast through the main, more permeable conduit. By a system of less permeable conduits which are associated with the main one, smaller quantities drain much more slowly. From the doline above Pivka Jama two highly permeable conduits lead through 40 m thick rock draining a significant amount of water. Around them several smaller conduits exist. The recharge area of the trickles is connected but their mutual links are of various permeabilities.
Keywords: hidrogeologija; karst; kraške vode; kraški pojavi; padavine; Pivka jama; Planina Cave; Planinska jama; sledenje; vrtače